Preliminary results of trial NPC‐0501 evaluating the therapeutic gain by changing from concurrent‐adjuvant to induction‐concurrent chemoradiotherapy, changing from fluorouracil to capecitabine, and changing from conventional to accelerated radiotherapy fractionation in patients with locoregionally advanced nasopharyngeal carcinoma. Issue 8 (19th December 2014) - Lee, Anne W.M.; Ngan, Roger K.C.; Tung, Stewart Y.; Cheng, Ashley; Kwong, Dora L.W.; Lu, Tai‐Xiang; Chan, Anthony T.C.; Chan, Lucy L.K.; Yiu, Harry; Ng, Wai‐Tong; Wong, Frank; Yuen, Kam‐Tong; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND A current recommendation for locoregionally advanced nasopharyngeal carcinoma (NPC) is conventional fractionated radiotherapy with concurrent cisplatin plus adjuvant cisplatin and fluorouracil (PF). In this randomized trial, the authors evaluated the potential therapeutic benefit from changing to an induction‐concurrent chemotherapy sequence, replacing fluorouracil with oral capecitabine, and/or using accelerated rather than conventional radiotherapy fractionation. METHODS Patients with stage III through IVB, nonkeratinizing NPC were randomly allocated to 1 of 6 treatment arms. The protocol was amended in 2009 to permit confining randomization to the conventional fractionation arms. The primary endpoint was progression‐free survival. Secondary endpoints included overall survival and safety. RESULTS In total, 803 patients were accrued, and 706 patients were randomly allocated to all 6 treatment arms. Comparisons of induction PF versus adjuvant PF did not indicate a significant improvement. Unadjusted comparisons of induction cisplatin and capecitabine (PX) versus adjuvant PF indicated a favorable trend in progression‐free survival for the conventional fractionation arm (P = .045); analyses that were adjusted for other significant factors and fractionation reflected a significant reduction in the hazards of disease progression (hazard ratio [HR], 0.54; 95% confidence interval [CI], 0.36‐0.80) and death (HR, 0.42; 95% CI, 0.25‐0.70). Unadjusted comparisons of induction sequences versus adjuvant sequences did not reach statistical significance, but adjusted comparisons indicated favorable improvements by induction sequence. Comparisons of induction PX versus induction PF revealed fewer toxicities (neutropenia and electrolyte disturbance), unadjusted comparisons of efficacy were statistically insignificant, but adjusted analyses indicated that induction PX had a lower hazard of death (HR, 0.57; 95% CI, 0.34‐0.97). Changing the fractionation from conventional to accelerated did not achieve any benefit but incurred higher toxicities (acute mucositis and dehydration). CONCLUSIONS Preliminary results indicate that the benefit of changing to an induction‐concurrent sequence remains uncertain; replacing fluorouracil with oral capecitabine warrants further validation in view of its convenience, favorable toxicity profile, and favorable trends in efficacy; and accelerated fractionation is not recommended for patients with locoregionally advanced NPC who receive chemoradiotherapy. Cancer 2015;121:1328–1338. © 2014 American Cancer Society.